STUDI FENOMENOLOGI: GAMBARAN PERKAWINAN SIRRI TERHADAP HAK PEREMPUAN DAN ANAK DALAM ASUHAN KELUARGA DI KECAMATAN PULOLOR, KABUPATEN JOMBANG: Phenomenological Study: Overview Of Sirri Marriages On The Rights Of Women And Children In Family Care In Pulolor District, Jombang District - Ana Dyah Aliza; Bherty, Chanda paramitha; Faizah, Nur Laila (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Until now, unregistered marriage is still a quite widespread phenomenon and a problem in society. There are several factors behind people choosing to marry in unregistered marriages, which has an impact on families, especially women and children. One of the first frameworks for obtaining legal certainty in family cases is the registration of marriages in government civil records. This research aims to present an overview of the problem of unregistered marriages in Pulolor District, Jombang Regency. The method used is a descriptive qualitative approach through interviews and collecting documentation which was carried out at the KUA Pulolor District on 2-20 August 2023 with civil servants at KUA Pulolor. The results found that the laws and provisions are clear and focused, where legal protection for those carrying out marriages must be recognized in writing. Marriage registration and legal protection, especially for children and women, must be increasingly optimal. The importance of marriage registration is to protect the rights of women as wives and children in the household. Marriages that are not registered can result in losses for the fulfillment of rights and obligations, especially for women and children